Design Expert Supported Mathematical Optimization and Predictability Study of Buccoadhesive Pharmaceutical Wafers of Loratadine. (28th May 2013) - Chakraborty, Prithviraj; Dey, Surajit; Parcha, Versha; Bhattacharya, Shiv Sankar; Ghosh, Amitava
Abstract : Objective . The objective of this work encompasses the application of the response surface approach in the development of buccoadhesive pharmaceutical wafers of Loratadine (LOR). Methods . Experiments were performed according to a 3 2 factorial design to evaluate the effects of buccoadhesive polymer, sodium alginate (A ), and lactose monohydrate as ingredient, of hydrophilic matrix former (B ) on the bioadhesive force, disintegration time, percent (%) swelling index, and time taken for 70% drug release (t 70 % ). The effect of the two independent variables on the response variables was studied by response surface plots and contour plots generated by the Design-Expert software. The desirability function was used to optimize the response variables. Results . The compatibility between LOR and the wafer excipients was confirmed by differential scanning calorimetry, FTIR spectroscopy, and X-ray diffraction (XRD) analysis. Bioadhesion force, measured with TAXT2i texture analyzer, showed that the wafers had a good bioadhesive property which could be advantageous for retaining the drug into the buccal cavity. Conclusion . The observed responses taken were in agreement with the experimental values, and Loratadine wafers were produced with less experimental trials, and a patient compliant product was achieved with the concept of formulation by design.